2003
DOI: 10.1021/ic0348345
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Cationic Rhenium(V) and Technetium(V) Dioxo Complexes Containing Four N-Heterocyclic Carbene Ligands

Abstract: Cationic dioxorhenium and dioxotechnetium complexes of the composition [MO(2)(L(1))(4)](+) (L(1) = 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene) have been prepared from various starting materials and studied spectroscopically and by X-ray crystallography. The metal-carbon distances range from 2.216(4) to 2.232(4) A indicating mainly sigma-bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 38 publications
6
45
0
Order By: Relevance
“…Similar values have been reported for the ReϭO vibration in [ReO 2 (1,3- 6 ], [9] and in [ReO 2 (dppe) 2 ][I]. [10] (1)…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Similar values have been reported for the ReϭO vibration in [ReO 2 (1,3- 6 ], [9] and in [ReO 2 (dppe) 2 ][I]. [10] (1)…”
supporting
confidence: 85%
“…[9] Compound 1 is soluble in aromatic hydrocarbons such as benzene or toluene, while compound 2 is insoluble in toluene, dichloromethane, tetrahydrofuran or diethyl ether, and slightly soluble in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the results recently published by Abram and co-workers, who observed that the number of NHCs introduced in a series of oxorhenium complexes depends on the electron-donating nature of the carbene, the more electron-donating the carbene, the higher the number of ligands [13]. In this sense, 4,5-dimethyl substituted NHCs always provide complexes with general formula [ReOCl-(NHC) 4 ] 2+ [4,15] (complexes with less than four carbenes could not be obtained), while non-substituted and triazolylidene NHCs provide ReOCl 3 (NHC) 2 [5] and [ReO(OMe)-Cl 2 (NHC)(PPh 3 )], respectively.…”
Section: Resultssupporting
confidence: 92%
“…Although most of the NHC-metal complexes reported to date refer to late transition metals in low oxidation states, a few examples concerning the coordination of these ligands to high oxidation state species have been reported [3][4][5]. Regarding the studies of N-heterocyclic carbene complexes of molybdenum, these are scarce, and most of them concern carbonyl molybdenum (0) complexes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Such ligands have been used in the coordination chemistry of many transition metals for quite a long time, but the first well-characterized rhenium and technetium compounds were not published until 2003. 36 This is surprising, particularly in the light that some of the compounds possess remarkable stability, which is mainly determined by the high sterical demand of the ligands systems, which protect the metal centers and prevent further ligand exchange and/or hydrolysis. The influence of ligand substituents has been carefully studied for oxorhenium(V) complexes with a series of 1,3-dialkyl-4,5-dimethylimidazol-2-ylidenes.…”
Section: (No)]mentioning
confidence: 99%